Realizing the Basic Income: Competing Claims to Expertise in Transformative Social Innovation - Pel, Bonno; Backhaus, Julia (Science & Technology Studies, 2020)
Current social innovation initiatives towards societal transformations bring forward new ways of doing and organizing, but new ways of knowing as well. Their efforts towards realizing those are important sites for the investigation of contemporary tensions of expertise. The promotion of new, transformative ways of knowing typically involves a large bandwidth of claims to expertise. The attendant contestation is unfolded through the exemplar case of the Basic Income in which the historically evolved forms of academic political advocacy are increasingly accompanied by a new wave of activism. Crowd-funding initiatives, internet activists, citizen labs, petitions and referenda seek to realize the BI through different claims to expertise than previous attempts. Observing both the tensions between diverse claims to expertise and the overall co-production process through which the Basic Income is realized, this contribution concludes with reflections on the politics of expertise involved in transformative social innovation.
Number: 2 Num Pages: 83 Place: Tampere, Finland Publisher: European Association for the Study of Science and Technology Section: Article
Keywords: Co-production; Innovation sociale; Innovation sociale transformatrice; Libre accès; Politiques; Transformations